2022
DOI: 10.1021/acsami.2c06295
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electrochemical Performance of NTs-WS2@C Nanocomposites for Lithium-Ion and Sodium-Ion Batteries

Abstract: Even though WS2 nanotubes (NTs-WS2) have great potential as anode materials for lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs) thanks to their unusual layered structure, their conductivity and cycling stability are far from satisfactory. To tackle these issues, carbon-coated WS2 (NTs-WS2@C) nanocomposites were prepared through a facile synthesis method that involved precipitating a carbon precursor (20% sucrose) on WS2 nanotubes, followed by annealing treatment under an argon environment. Thanks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…This temperature range was chosen assuming residual APTES was removed below 200 °C. Knowing the specific surface area (SSA BET ) of the WS 2 NTs, 59 from BET measurements = 19.19 m 2 g −1 the coverage density ( σ ) can be readily calculated using eqn (3) and the values are listed in Table 1:…”
Section: Resultsmentioning
confidence: 99%
“…This temperature range was chosen assuming residual APTES was removed below 200 °C. Knowing the specific surface area (SSA BET ) of the WS 2 NTs, 59 from BET measurements = 19.19 m 2 g −1 the coverage density ( σ ) can be readily calculated using eqn (3) and the values are listed in Table 1:…”
Section: Resultsmentioning
confidence: 99%
“…The GCD profiles of SnCu 2 Se 4 /d-Ti 3 C 2 T x /NPC are presented in Figure b at 0.1 A g –1 , which deliver initial discharge and charge capacities of 780 and 609 mAh g –1 , respectively. The low initial coulombic efficiency (CE) of 78% may be attributed to the decomposition of the electrolyte and the formation of a solid electrolyte interface (SEI) film. The CEs improve to 94 and 96% in the following second and third cycles, respectively, suggesting the good reversibility of the SnCu 2 Se 4 /d-Ti 3 C 2 T x /NPC anode for Li + insertion/extraction.…”
Section: Resultsmentioning
confidence: 99%
“…For alleviating the aforementioned deleterious properties, heterostructures of WS 2 NTs and carbon have been utilized in a recent study, where an improvement in the electrochemical properties of WS 2 NTs were observed. The investigation led by Zdeněk and co-workers showed that the NTs-WS 2 @C composite electrode sustained a capacity of 152 mA h g –1 after 60 cycles when tested at a current density of 80 mA g –1 in a sodium ion half-cell . However, such a capacity is insufficient to fulfill the need for application in modern technological devices.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation led by Zdeněk and co-workers showed that the NTs-WS 2 @C composite electrode sustained a capacity of 152 mA h g –1 after 60 cycles when tested at a current density of 80 mA g –1 in a sodium ion half-cell. 21 However, such a capacity is insufficient to fulfill the need for application in modern technological devices. An alternative hybridization method to minimize the shortcomings of TMD-based 1D structures is to functionalize them with polymer-derived ceramic materials (PDCs).…”
Section: Introductionmentioning
confidence: 99%